Analisa Pengendalian Kerusakan Kendaraan untuk Meminimalisasi Keterlambatan Pengiriman Barang dengan Menggunakan Metode Total Productive Maintenance (TPM) pada PT. Buwana Indonesia - Sofyan, Soleh (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2022)
Maintenance is a conception of all activities needed to maintain or maintain quality so that it can function properly as in its previous condition. This research was conducted in the Mechanical Division of PT. Buwana Indonesia unit of freight transport. The problem raised in this study is the low level of work productivity for freight cars resulting from the lack of planned maintenance or maintenance activities carried out. This research method used is Total Productive Maintenance (TPM) which is a philosophy that aims to maximize the effectiveness of the facilities used in the industry, which are not only addressed in maintenance but in all aspects of the operation and installation of production facilities including increased motivation of the people working in the company. The main objective of implementing TPM at PT. Buwana Indonesia is to identify and reduce the types of damage to critical components that are the object of research and to increase Overall Equipment Efficiency (OEE) as a performance measure of this research. From the results of the analysis carried out, the percentage of each criterion was obtained, namely raw material criteria 47.10%, engine capacity criteria 21.80%, labor criteria 16.20% and product quality criteria 14.9%. It can be seen that the criterion that has the greatest influence on productivity in the Converting section, the first is the raw material criterion, the second is the engine capacity criterion, the third is the labor criterion, and the last is the product quality criterion.